2020
DOI: 10.1155/2020/6734048
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis Revealed the Potential Gene Regulatory Processes of ATRA-Triggered Neuroblastoma Differentiation and Identified a Novel RA Response Sequence in theNTRK2Gene

Abstract: Retinoic acid- (RA-) triggered neuroblastoma cell lines are widely used cell modules of neuronal differentiation in neurodegenerative disease studies, but the gene regulatory mechanism underlying differentiation is unclear now. In this study, system biological analysis was performed on public microarray data from three neuroblastoma cell lines (SK-N-SH, SH-SY5Y-A, and SH-SY5Y-E) to explore the potential molecular processes of all-trans retinoic acid- (ATRA-) triggered differentiation. RT-qPCR, functional genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Similar results were presented in a recent study, where no significant changes were found in MAP2 and SYP transcript levels in SH-SY5Y cells in response to RA treatment, despite the changes in cell morphology and MAP2 staining pattern observed by immunocytochemistry. [36] Additionally, MAP2 and SYP were not identified among the significantly regulated genes in previous microarray and RNA-seq transcriptional profiling studies of RA-treated SH-SY5Y cells. [33,37] These are presented (three biological replicates per experiment).…”
Section: Sh-sy5y Cell Morphology and Phenotypementioning
confidence: 82%
See 1 more Smart Citation
“…Similar results were presented in a recent study, where no significant changes were found in MAP2 and SYP transcript levels in SH-SY5Y cells in response to RA treatment, despite the changes in cell morphology and MAP2 staining pattern observed by immunocytochemistry. [36] Additionally, MAP2 and SYP were not identified among the significantly regulated genes in previous microarray and RNA-seq transcriptional profiling studies of RA-treated SH-SY5Y cells. [33,37] These are presented (three biological replicates per experiment).…”
Section: Sh-sy5y Cell Morphology and Phenotypementioning
confidence: 82%
“…Similar results were presented in a recent study, where no significant changes were found in MAP2 and SYP transcript levels in SH‐SY5Y cells in response to RA treatment, despite the changes in cell morphology and MAP2 staining pattern observed by immunocytochemistry. [ 36 ] Additionally, MAP2 and SYP were not identified among the significantly regulated genes in previous microarray and RNA‐seq transcriptional profiling studies of RA‐treated SH‐SY5Y cells. [ 33,37 ] These studies highlighted the upregulation of several transcription required for neuronal differentiation, but no significant changes were detected in structural or synaptic markers at the transcriptional level, [ 33,37 ] although increases in MAP2 and SYP expression in differentiated SH‐SY5Y cells were observed by immunostaining and immunoblotting.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression and activity of several GFRs, including RET, EGFR, TrkA, and TrkB, have been associated with neuroblastoma differentiation. [95][96][97][98][99][100][101][102][103][104][105][106][107][108] While further studies are clearly needed to determine the relative roles of individual intracellular and extracellular pathways and of individual genes within each cluster, our data demonstrating the association of UBE4B with neuroblastoma differentiation suggests that UBE4B-mediated signaling may play a key role in the differentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells are SKN-SH human neuroblastoma cell line [ 16 ] sub-clones and were purchased from Pasteur Institute (Tehran, Iran). Cells were cultured at an initial seeding density of 10 4 cells/cm 2 in the wells of the chip, which had been coated with laminin (0.01 mg ml ) over the Poly-D-lysine layer (0.05 mg ml ).…”
Section: Methodsmentioning
confidence: 99%